Fly ash: An alternative cheap source material for seepage control in soil conservation structure - PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2020)
Fly ash is now used as a pozollanic substitute for cement in roller compacted concrete dams-an innovative dam technology developed as an outcome of efforts to design more economical concrete dams. Fly ash is used in reinforced cement concrete (R.C.C.) structures not only for saving cement cost but also for enhancing strength and durability. However, it is obvious that the control of seepage through either the embankment above ground level or the foundation of it is of very much significance from engineering point of view. Seepage through the embankment above ground level and foundation of a hydraulic structure makes it weak and subsequently causes breach and collapse it. In case of earthen and rock fill dams, this seepage resistance is achieved by providing core wall in the embankment above ground level and cut-off triangular or trapezoidal notch and compact with clay-mud or cement concrete base in the foundation of the dam structure. Sometimes, the foundation seepage is controlled by providing upstream fore shore blanket. This seepage is controlled by using relatively impermeable materials like cement for the core wall, cut-off and upstream blanket. But use of cement alone in the core wall and cut-off of foundation of the embankment of the dam, involve the cost of construction. Fly-ash, though permeable, can be made relatively impermeable by adding cement with it and this mixture of cement and fly ash in the core wall and cut-off of hydraulic structure minimises cost of construction of the structure and also increases its strength. To achieve these objectives an effort has been made to study the effect of cement on the permeability of fly-ash collected from NALCO thermal power station, Anugul, Odisha. It has been observed that the permeability of fly-ash reduces with increase of percentage of cement mixed with it. The result of present investigation suggests that, mixing of 15% of with the fly-ash gives practically the lowest permeability as against value of permeability which is found to be in the initial range of the permeability of clay. In order to test the strength of these mixtures for use in hydraulic structures, a comparison of compressive strength, cohesive strength and load of failure of cubes of fly-ash mixed with cement at various percentages ranging from 5 to 15% have also been made which show that fly-ash mixed with cement can be used safely in earthen embankments for effective seepage control.